If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(c + -6) = -15 Reorder the terms: 5(-6 + c) = -15 (-6 * 5 + c * 5) = -15 (-30 + 5c) = -15 Solving -30 + 5c = -15 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + 5c = -15 + 30 Combine like terms: -30 + 30 = 0 0 + 5c = -15 + 30 5c = -15 + 30 Combine like terms: -15 + 30 = 15 5c = 15 Divide each side by '5'. c = 3 Simplifying c = 3
| (2x+9)^1/3+1=0 | | 6y-1=2(3y-2) | | 4+y=7+5y | | 1/5x+6=12 | | y=24500-200x | | -2x+6x=24 | | 6+8=x-1 | | h=160-16t^2 | | 13x=-20+85 | | 5x+2.3=9.3 | | 3r+7r=140 | | -(m+4)=2 | | 1/2x+5=18 | | 3(w-6)=27 | | -0.9x+1.29=-0.5x+3.29 | | 2d=a-b/b-c | | -7x+8=22 | | -y+2=-19 | | 3l-6=8l-4(3l-2) | | (x+5)(x)=8 | | 6=-2x+2 | | 6+9c=3c+47 | | 8/4 | | 4x+1.3=6.1 | | -1+0.2(30)=x | | x+35/x+8=4 | | 2a=124 | | 7x-17=-52 | | 73-6x=3x+22 | | y=x^2-16x+2 | | -1+0.2(20)=x | | -5.1=0.9-2y |